Unveiling the Influence of Perceived Organizational Support on Work Engagement and Organizational Citizenship Behavior - Ni, Sudiyani Nyoman; Rihayana, I Gede (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 18 Nomor 2 Tahun 2024DO - 10.24843/MATRIK:JMBK.2024.v18.i02.p05, 2024)
The hospitality industry in Bali has shown significant recovery after the impact of COVID-19. However, the industry is experiencing substantial changes in operations and human resource management strategies, one of which is the importance of employees exhibiting extra-role behaviors. This study explores the relationship between Perceived Organizational Support (POS), work engagement (WE), and organizational citizenship behavior (OCB) in four-star accommodation in Bali, where the results of a study of 130 hotel employees showed that WE mediates the relationship between POS and OCB. POS significantly influenced OCB and WE. The research findings specifically show that POS is very important in promoting OCB. This study uses social exchange theory to emphasize that POS can increase WE and OCB. This suggests that the role of the organization is crucial in ensuring employees feel valued and cared for in terms of their assistance and welfare.  Keywords : organizational citizenship behavior; perceived organizational support; work engagement